Bone marrow-derived progenitor cells do not contribute to podocyte turnover in the puromycin aminoglycoside and renal ablation models in rats - Meyer-Schwesinger, Catherine; Lange, Claudia; Broecker, Verena; Agustian, Putri Andina; Lehmann, Ulrich; Raabe, Annette; Brinkmeyer, Martina; Kobayashi, Eiji; Schiffer, Mario; Buesche, Guntram; Kreipe, Hans H.; Thaiss, Friedrich; et al. (American Journal of Pathology, 2011)
A key event in the progression of glomerular disease is podocyte loss that leads to focal and segmental glomerulosclerosis (FSGS). Because adult podocytes are postmitotic cells, podocyte replacement by bone marrow-derived progenitors could prevent podocytopenia and FSGS. This study uses double immunofluorescence for Wilms' tumor-1 and enhanced green fluorescent protein (eGFP) to examine whether an eGFP-positive bone marrow transplant can replace podocytes under normal circumstances and in 3 different rat models of FSGS: puromycin aminoglycoside nephropathy, subtotal nephrectomy, and uninephrectomy. Bone marrow engraftment was successful, with more than 70% eGFP-positive cells and virtually normal histologic findings. No bone marrow transplant-derived podocytes were found in four control rats after transplantation, in nine rats at up to 10 weeks after puromycin aminoglycoside nephropathy induction, in three rats 23 days after subtotal nephrectomy, and in six rats up to 21 days after uninephrectomy. A total of 2200 glomeruli with 14,474 podocytes were evaluated in all groups. Thus, podocyte replacement by bone marrow-derived cells does not contribute to podocyte turnover in rats, even in models of podocyte damage. This is in contrast to previous studies in mice, in which bone marrow-derived podocytes were found. Further studies will address this discrepancy, which could be explained by species differences or by predominant podocyte regeneration from a parietal epithelial cell niche. Copyright © 2011 American Society for Investigative Pathology. Published by Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2020-11-12